Maximum length sequences-auditory brainstem responses from children with auditory processing disorders - Jirsa, R.E. (Journal of the American Academy of Audiology, 2001)
This study was designed to evaluate maximum length sequences-auditory brainstem responses (MLS-ABR) in children with auditory processing disorders and to compare these results with a normal control group matched for age, intelligence, and gender. Although each waveform was analyzed for the presence of waves I, III, and V, the primary focus was wave V. Although absolute latency measures for wave V were obtained from all subjects, waves I and III were not always identified. Although the results showed latency increases for all waveforms in both groups, the only significant difference noted was an increase in wave V latency for both the left and right ears in the clinical group. These results suggest that the MLS-ABR may be useful in the assessment of auditory processing disorders. Implications for the potential use of the MLS-ABR in management programs are discussed.
Keywords: *Evoked Potentials, Auditory, Brain Stem/ph [Physiology]; *Hearing Disorders/di [Diagnosis]; Adolescent; Auditory brainstem response; Auditory evoked potentials; Auditory processing disorders; Child; Evoked Potentials, Auditory, Brain Stem; Female; Hearing Disorders; Hearing Disorders/ep [Epidemiology]; Hearing Tests; Humans; Male; Maximum length sequences; Random Allocation; Speech Perception; Speech Perception/ph [Physiology]; Time Factors; adolescent; age; article; child; clinical article; comparative study; controlled study; dept.cmd; evoked brain stem auditory response; female; gender; hearing impairment; human; intelligence; latent period; male; medical assessment; peer-reviewed; priority journal; sensory system electrophysiology; waveform

Recovery of communication skills following intracerebral hemorrhage: A case study - Purdy, MH (Journal of Medical Speech-Language Pathology, 2001)
Numerous variables contribute to the ultimate recovery of communication skills following neurological damage. This report provides a review of the literature pertaining to prognostic indicators and chronicles the recovery of communication skills in a 48-year-old man who sustained a left intracerebral hemorrhage over a 29-month period.
Keywords: adult; article; brain hemorrhage; case report; communication disorder; dept.cmd; human; male; priority journal; prognosis; skill; speech rehabilitation; treatment outcome; ⛔ No DOI found

Psycholinguistic models of speech development and their application to clinical practice - Baker, Elise; Croot, Karen; Mcleod, Sharynne; Paul, Rhea (Journal of Speech Language and Hearing Research, 2001)
This article presents an introduction to psycholinguistic models of speech development. Two specific types of models are addressed: box-and-arrow models and connectionist or neural network models. We review some historical and some current models and discuss recent applications of such models to the management of speech impairment in children. We suggest that there are two ways in which a psycholinguistic approach can influence clinical practice: by directly supplementing a speech-language pathologist's repertoire of assessment and treatment approaches and by offering a new way to conceptualize speech impairment in children.
Keywords: Assessment; Brain; Child Language; Child, Preschool; Connectionist models; Humans; Impairment; Language Disorders; Neural Networks (Computer); Psycholinguistic models; Psycholinguistics; Speech; Speech development; Verbal Learning; article; artificial neural network; brain; dept.cmd; human; language development; language disability; learning; linguistics; pathophysiology; preschool child; speech